2016
DOI: 10.1007/s00586-016-4757-0
|View full text |Cite
|
Sign up to set email alerts
|

The cranial sagittal vertical axis (CrSVA) is a better radiographic measure to predict clinical outcomes in adult spinal deformity surgery than the C7 SVA: a monocentric study

Abstract: The clinical correlation effect of outcome scores to the CrSVA measures is validated. Global SVA has an especially strong correlation with ODI and all the SRS subscores. Our study confirms that CrSVA is a stronger predictor of preoperative clinical outcomes than the C7 SVA in adult deformity patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Understanding sagittal balance provides the most appropriate choice [52]. Sagittal balance is a dynamic phenomenon, and it is better to have a good sagittal balance (even compensated) than a good sagittal alignment with a long fusion and no ability to compensate [39,53]. This is the reason why we came to the conclusion that the recent papers providing rules to tolerate increased pelvic tilt and SVA in elderly is probably not appropriate.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Understanding sagittal balance provides the most appropriate choice [52]. Sagittal balance is a dynamic phenomenon, and it is better to have a good sagittal balance (even compensated) than a good sagittal alignment with a long fusion and no ability to compensate [39,53]. This is the reason why we came to the conclusion that the recent papers providing rules to tolerate increased pelvic tilt and SVA in elderly is probably not appropriate.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…But we found no signi cant differences between the preoperative value and the ultimate follow-up value in CrSVA-S and CrSVA-H, which means C7SVA is less sensitive than CrSVA-S and CrSVA-H in detecting mild deterioration of global sagittal balance. It was also reported CrSVA was more correlated with ODI and all SRS subscores than C7SVA [7], which could not consider the motion of cervical spine[21]. But we still think further investigation of cranial parameters is warranted to clarify their meaning as global alignment parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The radiographic parameters included (1) C7 sagittal vertical axis(C7SVA); the distance between the vertical plumb line centered in the middle of C7 vertebral body and the posterosuperior corner of S1, (2) Cranial-sagittal vertical axis-hip(CrSVA-H); the distance between the vertical plumb line from the cranial center of gravity(CCG) to the centers of femoral heads [7], (3) Cranial-sagittal vertical axis-Sacrum(CrSVA-S); the distance between the vertical plumb line from the CCG to the posterosuperior corner of S1 [7], (4) Cervical lordosis(CL); the angle created by a line parallel to the inferior endplate of C2 and a line parallel to the inferior endplate of C7, (5) Thoracic kyphosis(TK); the angle created by a line parallel to the inferior endplate of T5 and a line parallel to the inferior endplate of T12, (6) Thoracolumbar kyphosis(TLK); the angle created by a line parallel to the superior endplate of T10 and a line parallel to the inferior endplate of L2, (7) Lumbar lordosis(LL); the angle created by a line parallel to the superior endplate of L1 and a line parallel to the endplate of S1, (8) Pelvic tilt(PT); the angle between the vertical line connecting the midpoint of the sacral plate to the femoral head axis and the vertical axis. For all sagittal measurements, the angle was de ned to be negative if the curve was lordotic and positive if the curve was kyphotic.…”
Section: ) Radiographic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have already demonstrated that the improvement in sagittal balance using the C7 SVA is the strongest predictor of improved outcomes in patients with adult spinal deformity [3][4][5][6], but Kim et al considered the cranial sagittal vertical axis (CSVA) is a better radiographic measure to predict clinical outcomes in adult spinal deformity surgery than C7 SVA [7].…”
Section: Introductionmentioning
confidence: 99%